Regional primary health care organisations and migrant and refugee health: the importance of prioritisation, funding, collaboration and engagement. (12th February 2020) - Ziersch, Anna; Freeman, Toby; Javanparast, Sara; Mackean, Tamara; Baum, Fran
Abstract: Objective : This paper examines whether Australian regional primary health care organisations – in this case, Medicare Locals (MLs) and Primary Health Networks (PHNs) – have engaged with migrant and refugee health, and what factors encourage work in this area. Methods: The study used mixed methods with surveys of ML (N=210) and PHN staff (N=66), interviews with ML (N=50) and PHN (N=55) staff, national consultations with migrant and refugee organisations (N=8 groups with 62 participants), and analysis of ML and PHN documents. Results : Needs assessment documents identified migrant and refugee health issues in 46% of MLs and 74% of PHNs. However, 48% of MLs and 55% of PHNs did not report any activities on migrant health, and 78% and 62% did not report any activities for refugees, respectively. Key factors identified by participants as associated with whether ML and PHN focus on migrant and refugee health were the determination of local priority areas, policy context and funding, collaboration with migrant and refugee organisations and communities, and mechanisms for engagement. Conclusions : Despite the importance of primary health care for migrants and refugees, there was relatively little attention paid to these population groups in MLs and PHNs, with a small number of notable exceptions. Implications for public health : The paper concludes with a range of recommendations for improving regional primary health care organisation engagement with migrant and refugee health.